Pollination: How to get the best deal - Byers, Kelsey JRP; Schiestl, Florian P (eLife, 2015)
Floral scents and nectar attract both pollinators and other animals that may reduce the plant's fitness, and therefore put flowering plants in a challenging situation.
Keywords: Nicotiana attenuata; Manduca sexta; Hyles lineata; Archilochus alexandri; Manduca quinquemaculata; pollination